The Industrialized Designer - Armstrong, Leah (Manchester University Press, 2024)
What does it mean to be called an industrial designer? This book traces the remarkable rise of this professional identity in historical perspective from a position of anonymity in the early twentieth century, to mid-century professionalisation, to decline and disintegration by 1980.